Analisis Kapasitas Dukung dan Penurunan Pondasi Berdasarkan Hasil Uji CPT (Studi Kasus Kawasan Pesisir Pantai Pulau Zum-zum) - Fitro Darwis; Elfira Resti Mulya; Sofyan Djafar (Fakultas Teknik, 2022)
In order to support Zum-zum Island as a tourism development area in Morotai Island Regency, a well - defined planning for developing basic infrastructure is required. Foundation is a construction base of a building structure which transmits the load from the top to the layer below it. This research was conducted at Zum - Zum Beach using CPT (Cone Penetration Test). An analysis was carried out on the bearing capacity and settlement of the footing and pile foundations. The results of the analysis show that the bearing capacity of the footing foundation has a varying value depending on the width of the foundation. The greater the width of the foundation with the same type and depth, the greater the bearing capacity of the foundation permit. Meanwhile, the bearing capacity of the pile foundation permit depends on the end resistance of the foundation and diameter of the pile. The immediate settlement of the foundation on sandy soil for the largest shallow foundation is 10.24 cm with a foundation width of 0.7 m. As for the depth foundation, the magnitude of the settlement is 0.40 cm on the pile with a diameter of 0.4 m.